2016
DOI: 10.1080/15389588.2016.1203426
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of railway trespassing by automatic sound warning—A pilot study

Abstract: The current study concludes that automatic sound warning may be efficient and cost effective at locations where fencing is not a viable option. However, it is not likely to be a cost-effective panacea for all kinds of sites where trespassing occurs, especially in countries like Finland where trespassing is scattered along the railway network rather than concentrated to a limited number of sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The number of trespassers was reduced by 44% at location A and 18% at location B, with a 95% level of confidence. The measures could be more efficient if they were combined with other preventive measures and at the location where the trespassing is concentrated [104]. In Finland, a 45-min lesson was held for children aged 8-11 years old in four schools.…”
Section: Pilot Studies Of Railway Trespassing Preventive Measuresmentioning
confidence: 99%
“…The number of trespassers was reduced by 44% at location A and 18% at location B, with a 95% level of confidence. The measures could be more efficient if they were combined with other preventive measures and at the location where the trespassing is concentrated [104]. In Finland, a 45-min lesson was held for children aged 8-11 years old in four schools.…”
Section: Pilot Studies Of Railway Trespassing Preventive Measuresmentioning
confidence: 99%
“…26 However, the evidence for the effectiveness of such measures is currently more limited. [27][28][29][30] Online, we saw how people appeared to be dissuaded from a road-related method by community members who stressed the potential lethal impact on other people. Although this may be effective in a closed, peer-led discussion, it is a difficult message to employ more widely because of the risk of appearing to dismiss or stigmatise the distress of the suicidal individual.…”
Section: Discussionmentioning
confidence: 99%
“…27 The RESTRAIL field trial conducted by VTT at two trespassing hotspots in Finland has indicated a significant effect of video enforcement combined with sound warnings: trespassing behaviour decreased by 44% at one hotspot and 18% at the other one. 46 These studies indicate that both education and enforcement measures should be used in combination with engineering measures, where the latter should create an environment that discourages illegal behaviours.…”
Section: Enforcement Measuresmentioning
confidence: 99%